Reduced C9orf72 expression exacerbates polyGR toxicity in patient iPSC-derived motor neurons and a Type I protein arginine methyltransferase inhibitor reduces that toxicity - Dane, Therese L.; Gill, Anna L.; Vieira, Fernando G.; Denton, Kyle R. (Frontiers in Cellular Neuroscience, 2023)
Intronic repeat expansions in the C9orf72 gene are the most frequent known single genetic causes of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). These repeat expansions are believed to result in both loss-of-function and toxic gain-of-function. Gain-of-function results in the production of toxic arginine-rich dipeptide repeat proteins (DPRs), namely polyGR and polyPR. Small-molecule inhibition of Type I protein arginine methyltransferases (PRMTs) has been shown to protect against toxicity resulting from polyGR and polyPR challenge in NSC-34 cells and primary mouse-derived spinal neurons, but the effect in human motor neurons (MNs) has not yet been explored. To study this, we generated a panel of C9orf72 homozygous and hemizygous knock-out iPSCs to examine the contribution of C9orf72 loss-of-function towards disease pathogenesis. We differentiated these iPSCs into spinal motor neurons (sMNs) and found that reduced levels of C9orf72 exacerbate polyGR15 toxicity in a dose-dependent manner. Type I PRMT inhibition was able to partially rescue polyGR15 toxicity in both wild-type and C9orf72-expanded sMNs.